The Mediating Role of Organizational Behavior of MSMEs in the Influence of Proactivity on Competitive Advantage (An Empirical Study of Quail Farming MSMEs in Bendowulung Village - Eko Adi Susilo; Novi Catur Muspita Sayehu; Sulistyo Anjarwati (Bulletin of Community Engagement, 2026)
The purpose of the Study: To examine and analyze the mediating role of organizational behavior of MSMEs in the influence of proactivity on competitive advantage (An Empirical Study of Quail Farming MSMEs in Bendowulung Village, Sanankulon District, Blitar Regency). Method Design and Sample: This quantitative study, based on the research problems and objectives, employs an explanatory research approach with a survey method. Data were collected from 60 quail farmers who served as the research sample. The data collection used a random sampling technique among quail farming MSMEs in Bendowulung Village, Sanankulon District, Blitar Regency. Data analysis was conducted using the Partial Least Squares (PLS) approach with SmartPLS software. Results: Proactivity was found to have a significant influence on competitive advantage, as supported by the findings of this study. An increase in proactivity leads to an increase in competitive advantage. Proactivity also significantly influences organizational behavior; the higher the level of proactivity, the stronger the organizational behavior. Additionally, organizational behavior significantly affects competitive advantage, indicating that improved organizational behavior leads to higher competitive advantage. Proactivity influences competitive advantage through organizational behavior, as evidenced by the Specific Indirect Effect analysis, which shows a p-value of less than 0.05 (0.000 < 0.05) for the indirect effect. Therefore, companies should enhance both proactivity and organizational behavior to strengthen their competitive advantage. Companies can promote positive organizational behavior and develop appropriate strategies to foster proactivity and enhance competitive advantage.